2007
DOI: 10.1111/j.1399-3054.2006.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the mode of binding of nitrite and the energy distribution between the two photosystems

Abstract: The reversibility of nitrite‐induced inhibition in relation to energy distribution between the two photosystems was studied in spinach thylakoid membranes. Measurements of electron transfer rate catalyzed by photosystem I (PS I) and photosystem II (PS II), chlorophyll a (Chl a) fluorescence induction kinetics, S2 state multiline spectra, and room temperature electron paramagnetic resonance (EPR) signals indicated that nitrite anions bind PS II in two ways: dissociable (loose) and non‐dissociable (tight). The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…2), indicating that the primary site of inhibition is localized to PSII rather than PSI or the intersystem electron transport (ET) components. Previous studies demonstrated that nitrite treatment inhibits the electron transport through PSII and stimulates electron flow through PSI by causing redistribution of the absorbed light energy in favor of the PSI (26,28). Therefore, we contend that the PSII electron transfer was damaged more seriously than the wholechain electron transfer and that the difference was possibly due to redistribution of absorbed excitation energy between two photosystems.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…2), indicating that the primary site of inhibition is localized to PSII rather than PSI or the intersystem electron transport (ET) components. Previous studies demonstrated that nitrite treatment inhibits the electron transport through PSII and stimulates electron flow through PSI by causing redistribution of the absorbed light energy in favor of the PSI (26,28). Therefore, we contend that the PSII electron transfer was damaged more seriously than the wholechain electron transfer and that the difference was possibly due to redistribution of absorbed excitation energy between two photosystems.…”
Section: Discussionmentioning
confidence: 72%
“…In the presence of excess nitrite, organisms can accumulate toxic levels of NO 2 Ϫ (24)(25)(26). Previous research showed that isolated chloroplasts subjected to high concentrations of nitrite exhibited decreased chlorophyll (Chl) contents, restricted photosynthetic electron transfer rates (27), and redistribution of absorbed excitation energy between the two photosystems (PS) (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the low chl a/b ratio in the Zn deficiency stressed leaves, the low Fv/Fm ratio may suggest a high ratio of PS II to PS I reaction centers in Erjiufeng. Similar to Fv/Fm, the Fv/Fo ratio also recorded a rapid decrease in Erjiufeng, which reflected lower efficiency of electron donation to PSII (Skorzynska and Baszynski 2000) and the structural alterations in PS II (Singh et al 2007).…”
Section: Discussionmentioning
confidence: 87%
“…The Fv/Fm ratio reflects quantum efficiency of primary photochemical reactions (Singh et al 2007). The rapid decrease in the Fv/Fm ratio occurred in the Zn‐deficient leaves of Erjiufeng indicates that this genotype possesses an intrinsic photochemical capacity far below that of controls, i.e., Zn deficiency induced significant impairment on the quantum yield of PS II in Zn‐inefficient Erjiufeng (Govindjee 1995).…”
Section: Discussionmentioning
confidence: 99%